The Narratives Of Resistance: The Role Of Literature In Social Movements In India - Prof. Sonba Salve (Kurdish Studies, 2022)
This Article aims to study the deep significance of literature in various contemporary social movements of India such as LGBTQ+ rights, Anti-CAA protests, and Environmental Activism. It explores how literary expressions disrupt the normal and work for the marginalized community and bring about solidarity. Issues of identity, belonging, and discrimination are clear themes in the work of authors like Arundhati Roy and emerging poets like Akshay P. S, while protest poetry and social media have amplified many dissenting voices. The piece also delves into the climbing importance of environmental literature, spotlighting writers like Rupi Kaur and Amitav Ghosh, who now use their literary power to write about the intersection between ecological and social justice. It is also a testament to the rise of new voices and different narratives contributing to the diversity of the literary landscape, advocating for empathy and understanding among different cultural enclaves. At its heart, this investigation verifies the significance of literature as a vehicle for change, community mobilization, and a better world of equity and justice.